2011
DOI: 10.1212/wnl.0b013e318206ca46
|View full text |Cite
|
Sign up to set email alerts
|

Circadian patterns of pediatric seizures

Abstract: Sleep and wakefulness, as well as time of day and night, are important considerations in proper characterization of seizure types and epilepsy localization. These findings may contribute to a better understanding of the mechanisms of nonrandom distribution of seizures, and may provide information for individualized treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 37 publications
3
116
0
Order By: Relevance
“…Most of the original studies described an increased seizure occurrence in the (early) morning compared to the rest of the day, both in epilepsy populations of all ages [31,34,35] and in cohorts including children [32,33,[36][37][38][39] or adults separately [40]. Many also reported a peak at varying times in the afternoon or the evening [32-37,39-45].…”
Section: Circadian Seizure Distributionmentioning
confidence: 99%
“…Most of the original studies described an increased seizure occurrence in the (early) morning compared to the rest of the day, both in epilepsy populations of all ages [31,34,35] and in cohorts including children [32,33,[36][37][38][39] or adults separately [40]. Many also reported a peak at varying times in the afternoon or the evening [32-37,39-45].…”
Section: Circadian Seizure Distributionmentioning
confidence: 99%
“…10,11 Many types of epileptic seizure occur according to a specific circadian rhythm. 12 Because of its location in the far north (i.e., north of 60 N), Finland has very long, bright summer days and very long, dark winter nights. In the city of Oulu in northern Finland, the length of the day as measured from sunrise to sunset on the winter solstice in December is only about 3.5 hours; on the summer solstice in June it is more than 22 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Loddenkemper et al 15 studied children with lesional focal epilepsy, and showed that frontal and parietal lobe seizures occurred mostly during sleep independent of day or night. Gurkas et al 16 described 170 patients (909 seizures) and found that frontal lobe seizures occurred more often at night and in sleep.…”
Section: Discussionmentioning
confidence: 99%